2018
DOI: 10.1080/00981389.2018.1455789
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer literacy and health beliefs related to breast cancer screening among American Indian women

Abstract: The purpose of this article is to examine the health beliefs and literacy about breast cancer and their relationship with breast cancer screening among American Indian (AI) women. Using the Health Belief Model (HBM) and hierarchical logistic regression with data from a sample of 286 AI female adults residing in the Northern Plains, we found that greater awareness of breast cancer screening was linked to breast cancer screening practices. However, perceived barriers, one of the HBM constructs, prevented such sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…A perceived barrier is the perception of factors that impede a health-related protective behavior or that make it difficult to display such a behavior [ 21 , 40 ]. These results were consistent with the literature [ 18 , 19 , 45 , 46 ], and it can be said that a high perception of the benefit and a low perception of the barriers play important roles in the regular achievement of screening behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…A perceived barrier is the perception of factors that impede a health-related protective behavior or that make it difficult to display such a behavior [ 21 , 40 ]. These results were consistent with the literature [ 18 , 19 , 45 , 46 ], and it can be said that a high perception of the benefit and a low perception of the barriers play important roles in the regular achievement of screening behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…[ 1 ] In particular, breast cancer is deemed as of the global health concerns[ 2 ] and the second leading cause to death worldwide. [ 3 ] In 2015, death estimates attributed to noncommunicable diseases according to the World Health Organization were 2,166,000 people/year, accounting for nearly 60% of total mortalities in the Eastern Mediterranean Region, where breast cancer comprises 23% of all cancers in women. [ 4 5 ] According to the Iranian Ministry of Health and Medical Education, breast cancer accounts for 16% of cancer cases, in which it is the primary cause in 7600 women.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that, while the majority of projects have used community engagement as a focus of research, others may not have taken it into account at all. When looking at the studies that scored 0 it was notable that none explicitly mentioned Indigenous researchers working on the study and nor did they view this as a limitation of their studies [ 30 , 33 , 37 ]. It should be noted that not all studies may have reported details of community engagement despite this being a key component of successful study design with Indigenous communities.…”
Section: Resultsmentioning
confidence: 99%